The effect of UV irradiation duty cycle on the 2nd harmonic coupling efficiency in optical fiber long period gratings - Barrington, James; Partridge, Matthew; James, Stephen W.; Tatam, Ralph P. (Elsevier, 2018)
Long period gratings (LPGs) as a sensing platform have the potential for multi-parameter measurement through the utilization of 2nd order coupling resonance bands. Although the current literature has produced LPGs with 2nd order resonance bands, the fabrication parameters required to generate these features have not been elucidated. Here, using UV irradiation via the point-by-point method, it is shown that by varying the duty cycle it is possible to fabricate LPGs that exhibit 2nd, 3rd, and 4th order coupling resonance bands. Fabrication of LPGs with a 25% or 75% duty cycle produces distinct 2nd order resonance bands, which are not observed when a 50% duty cycle is adopted.
Keywords: Optical fiber; Long period grating; Optical fiber filter; Optical fiber sensor